Analisis Sektor Unggulan Di Kabupaten Wonogiri Tahun 2011-2015 - Wulandari, Fitriana Nur, Ir.Maulidyah IH, M.Si (2017)
The data used in this research is secondary data in the form of regional gross domestic product (GDP) Wonogiri and gross regional domestic product (GRDP) of Central Java province on the basis of constant prices 2011-2015 were obtained from BPS Wongiri and Central Java Province. The analysis tool used is LQ and Shift Share Esteban Marquillas. The results showed that the leading sectors in Wonogiri based on test results Estebban Marquillas shift share analysis. Results LQ analysis shows agriculture, fisheries and forestry, transportation and warehousing, mining and quarrying, education services, other service sectors, the sector of wholesale and retail trade sector, health services and social activities, service sector companies, the financial services sector and insurance, public administration sector, and the sector pengadan water, waste management, waste and recycling is a sector basisi in Wonogiri. The sectors that have competitive advantages and specialized in Wonogiri based analysis Shift Share Esteban Marquillas are agriculture, forestry and fishing, mining and quarrying, water supply, waste management, waste and recycling sector, wholesale and retail trade, transportation and warehousing, financial services and insurance sector, the service sector enterprises, public administration, education services sector, the service sector of health and social activities other service sector.